2007
DOI: 10.1097/smj.0b013e3181583949
|View full text |Cite
|
Sign up to set email alerts
|

Child Overweight Interventions in Rural Primary Care Practice: A Survey of Primary Care Providers in Southern Appalachia

Abstract: Child overweight has reached an epidemic level throughout the United States. A total of 65 primary care providers in southern Appalachia were surveyed to understand current issues in addressing child overweight in rural primary care practice. The study shows that while providers realized the importance of child overweight intervention, many were not ready and did little to address child overweight in their practices. The providers' skill levels in addressing child overweight were generally less than sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Physicians’ current practices addressing childhood overweight and obesity were assessed with twelve items/activities, using the same questionnaire as the previous study 15. The twelve items are listed in Table 2 and were grouped into three categories: assessment, treatment, and follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicians’ current practices addressing childhood overweight and obesity were assessed with twelve items/activities, using the same questionnaire as the previous study 15. The twelve items are listed in Table 2 and were grouped into three categories: assessment, treatment, and follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…The Pearson correlation coefficient was calculated between each of the responses, assessment, treatment, and follow-up, and each of the predictors listed on Table 6. The questionnaire items on providers’ attitudes, skill levels, and barriers were adopted from a questionnaire developed by a group of experts consisting of researchers, clinicians, and health educators,11 and are the same as those used in the previous study 15. SPSS ® (SPSS, Inc., an IBM Company, Chicago, IL) software was utilized in the statistical analysis of the data 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this area has been characterized by a particularly high prevalence of overweight and poor health behaviors [23,24], a recent study revealed only a small portion of primary care providers address these issues in practice [25]. Therefore, designing interventions to meet the needs of providers and individuals in these populations may be especially important.…”
Section: Methodsmentioning
confidence: 99%
“…The health care provider questionnaire contains 61 items assessing provider’s 1) general demographic information such as gender, education, and years of practice, 2) attitudes toward managing childhood overweight, 3) perceived barriers in the treatment of overweight children, 4) perceived skill level, and 5) readiness in treating child overweight in his/her practice [25, 37]. …”
Section: Methodsmentioning
confidence: 99%